PERBANDINGAN HUKUM KETENTUAN PERKAWINAN POLIGAMI DI INDONESIA DAN MESIR - Raka Haikal Anfasya; Natasya Yunita Sugiastuti (Fakultas Hukum Universitas Trisakti, 2023)
According to Indonesian law, monogamy is the foundation of marriage, although this principle is not unbreakable but rather flexible. Marriage law sets forth strong guidelines and requirements for polygamous marriages in order to prevent violations of and injury to wives' rights and to generally safeguard women. This study compares the polygamy provisions based on Egyptian and Indonesian law to examine the polygamy issue. The research is normative, using secondary data, qualitative analysis, and deductive conclusion. Research findings: Indonesian law regarding polygamous marriages is more comprehensive and complex than Egyptian law. Here some characteristics of polygamous marriages: the husband asks permission to engage in polygamy from the court; there is an obligation of notification and permission from the first wife; a reason to practice polygamy; sanctions for parties who violate the provisions on polygamy. In conclusion, Muh.Irham's decision was proven to have abandoned Nurdiana because she remarried secretly and according to Article 45 (1) PP No.9 1975 Muh.Irham was threatened with a fine of Rp.7500. Meanwhile, Big Ramy was proven to have committed polygamy secretly and according to Article 23 Bis Law 100 of 1985 was threatened with imprisonment for 6 months and a fine of 200 (Two Hundred) Pounds.